The Relationship Between Nutritional Knowledge, Attitudes, and Food Choice Through Online food delivery among Culinary Students at UNESA - Rahmadia Faeda Musaid; Sri Handajani; Any Sutiadiningsih; Hidayatun Muyasyaroh (Universitas Negeri Padang, 2026)
The development of online food delivery services has influenced students consumption patterns and has the potential to reduce the quality of food choices due to ease of access and price promotions. Students in the transitional age to adulthood are a group that is vulnerable to nutritional problems, so choosing healthy foods is important. Healthy food choices are based on nutritional knowledge that shapes beliefs and is reflected in attitudes. The objectives of this study were: (1) to examine the relationship between nutritional knowledge and attitudes; (2) to examine the relationship between nutritional knowledge and food choices through online food delivery; (3) to examine the relationship between attitudes and food choices through online food delivery. This was a quantitative study with a cross-sectional approach conducted on 86 undergraduate students majoring in Culinary Education at Universitas Negeri Surabaya. The data were analyzed using Spearman's rank correlation test. The results showed a relationship between nutritional knowledge and attitudes (p = 0.039), no relationship between nutritional knowledge and food choice (p = 0.571), and a relationship between attitudes and food choice (r = 0.526; p < 0.001).